STRATEGI GURU PENDIDIKAN AGAMA KATOLIK DALAM MENANGGULANGI STRES AKADEMIK SISWA KELAS XI DI SMA SANTO ANTONIUS BANGUN MULIA MEDAN - Mimpin Sembiring; Gabriella Stefy Grav Sinaga (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT This research is motivated by the phenomenon of high academic demands that trigger psychological pressure in the form of academic stress among students, which manifests in physical, emotional, cognitive, and behavioral disturbances. The purpose of this study is to analyze the strategies of Catholic Religious Education teachers in managing academic stress experienced by grade XI students at SMA Santo Antonius Bangun Mulia Medan. The research method used is descriptive qualitative. The research subjects consisted of 12 informants, namely 10 grade XI students, 1 Catholic Religious Education teacher, and 1 school principal, who were selected using the snowball sampling technique. Data collection techniques were conducted through observation, in-depth interviews, and documentation, with data analysis comprising data reduction, data display, and conclusion drawing. The trustworthiness of the data was tested using source triangulation and technique triangulation. The results showed that the academic stress of grade XI students was evident from physical fatigue, sleep disturbances, easy irritability, difficulty concentrating, negative thoughts about oneself, and procrastination of school tasks. To overcome this condition, Catholic Religious Education teachers implement coping strategies through their roles as faith and moral educators, spiritual mentors, Christian life role models, facilitators of religious activities, builders of faith communities, and developers of Catholic Religious Education. The main conclusion of the study indicates that the humanistic, reflective, and Christian spirituality-based approach of Catholic Religious Education teachers can provide a positive influence in strengthening inner resilience, restoring learning motivation, and building students' peace of mind at school. ABSTRAK Penelitian ini dilatarbelakangi oleh fenomena tingginya tuntutan belajar yang memicu tekanan psikologis berupa stres akademik pada siswa, yang bermanifestasi pada gangguan fisik, emosional, kognitif, dan perilaku. Tujuan penelitian ini adalah untuk menganalisis strategi Guru Pendidikan Agama Katolik (PAK) dalam menanggulangi stres akademik yang dialami oleh siswa kelas XI di SMA Santo Antonius Bangun Mulia Medan. Metode penelitian yang digunakan adalah kualitatif deskriptif. Subjek penelitian terdiri atas 12 informan, yaitu 10 siswa kelas XI, 1 guru PAK, dan 1 kepala sekolah, yang ditentukan menggunakan teknik snowball sampling. Teknik pengumpulan data dilakukan melalui observasi, wawancara mendalam, dan dokumentasi, dengan analisis data melalui tahap reduksi data, penyajian data, dan penarikan kesimpulan. Keabsahan data diuji menggunakan triangulasi sumber dan triangulasi teknik. Hasil penelitian menunjukkan bahwa stres akademik siswa kelas XI tampak dari kelelahan fisik, gangguan tidur, mudah marah, sulit berkonsentrasi, pikiran negatif terhadap diri sendiri, serta prokrastinasi tugas sekolah. Untuk mengatasi kondisi tersebut, Guru PAK menerapkan strategi penanggulangan melalui perannya sebagai pendidik iman dan moral, pembimbing spiritual, teladan hidup Kristiani, fasilitator kegiatan keagamaan, pembangun komunitas beriman, serta pengembang Pendidikan Agama Katolik. Simpulan utama penelitian menunjukkan bahwa strategi pendekatan guru PAK yang humanis, reflektif, dan berbasis penguatan spiritualitas Kristiani mampu memberikan pengaruh positif dalam menguatkan ketahanan batin, memulihkan motivasi belajar, serta membangun ketenangan jiwa siswa di sekolah.